2014
DOI: 10.1093/mnras/stu2025
|View full text |Cite
|
Sign up to set email alerts
|

The variability of the Crab nebula in radio: no radio counterpart to gamma-ray flares

Abstract: We present new Jansky Very Large Array (VLA) radio images of the Crab Nebula at 5.5 GHz, taken at two epochs separated by 6 days about two months after a gamma-ray flare in 2012 July. We find no significant change in the Crab's radio emission localized to a region of < 2 light-months in radius, either over the 6-day interval between our present observations or between the present observations and ones from 2001. Any radio counterpart to the flare has a radio luminosity of < ∼ 2 × 10 −4 times that of the nebula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 50 publications
5
14
0
Order By: Relevance
“…Similar to the SE X-ray jet, the counter-jet appears to be hardly discernible in the radio images (see e.g., right panel in Fig. 3) but it stands out in the 2-epoch difference image produced by Bietenholz et al (2014) and shown in the bottom right panel of Figure 1. Finally, the counter-jet is so faint in X-rays (if preset at all) that it cannot be discerned from the torus emission.…”
Section: Multiwavelength Properties Of the Crabmentioning
confidence: 93%
“…Similar to the SE X-ray jet, the counter-jet appears to be hardly discernible in the radio images (see e.g., right panel in Fig. 3) but it stands out in the 2-epoch difference image produced by Bietenholz et al (2014) and shown in the bottom right panel of Figure 1. Finally, the counter-jet is so faint in X-rays (if preset at all) that it cannot be discerned from the torus emission.…”
Section: Multiwavelength Properties Of the Crabmentioning
confidence: 93%
“…Since they are poorly localized in gammarays, we obtained radio observations of the Crab following a gamma-ray flare in 2012 August to look for a radio counterpart. Our initial results are reported in Bietenholz et al (2015): we did not find any such radio counterparts. We did, however, obtain high-quality radio images of the Crab.…”
Section: Introductionmentioning
confidence: 61%
“…As already mentioned, we use the 2012 radio observations described in Bietenholz et al (2015). We give here only a brief description of the observations: there were two sessions of VLA observations on 2012 August 20 and 26, spaced 6 days apart (observing code 12A-486).…”
Section: Vla Observationsmentioning
confidence: 99%
“…We updated the VLA 1.4 GHz image from B1950 to J2000 coordinates. Due to the expansion of the supernova remnant, we have furthermore expanded the SNR's emission spatially by 3.11 % accounting for the expansion rate of 0.135 % per year (Bietenholz et al 2015) between the observing date (1987) and the reference epoch of WISE, Herschel and Planck observations (2010) 7 . Total integrated flux densities of 599.3 Jy and 833.77 Jy were inferred at 4.8 and 1.4 GHz, respectively.…”
Section: Millimetre and Radio Observationsmentioning
confidence: 99%